2019
DOI: 10.1039/c9nr05919a
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in two-dimensional materials and their nanocomposites in sustainable energy conversion applications

Abstract: Two-dimensional (2D) materials have a wide platform in technical studies and expanding nano- and atomic-level applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
134
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 232 publications
(134 citation statements)
references
References 402 publications
0
134
0
Order By: Relevance
“…It acts as an additional reducing agent with Se during the growth of nanosheets and thin films when elemental Se and metal oxides are used as precursors. 7 But in our case, the absence of H 2 as a reducing agent simplified our synthetic procedure and dismissed the possibility of having H 2 Se (very toxic gas) as a byproduct. It also indicated that the synthesis could take place only with a simply diluted acid etching (taking 0.01 (M) of HCl) of the W foil before selenization.…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…It acts as an additional reducing agent with Se during the growth of nanosheets and thin films when elemental Se and metal oxides are used as precursors. 7 But in our case, the absence of H 2 as a reducing agent simplified our synthetic procedure and dismissed the possibility of having H 2 Se (very toxic gas) as a byproduct. It also indicated that the synthesis could take place only with a simply diluted acid etching (taking 0.01 (M) of HCl) of the W foil before selenization.…”
Section: Resultsmentioning
confidence: 81%
“… 4 6 A controllable synthesis of 2D materials with high quality and high efficiency is essential for their large-scale applications, for instance, their functions as electrode material in batteries. 7 There are many methods for the synthesis of two-dimensional materials, including mechanical exfoliation, 8 liquid exfoliation, 9 liquid-phase routes, 1 , 10 and chemical vapor deposition (CVD). 11 , 12 Among these processes, CVD offers better quality, efficiency, consistency, and control over the others.…”
Section: Introductionmentioning
confidence: 99%
“…One closely associated category of 2D crystals is single element 2D Xenes, which obtain their etymology from sp 2 ‐hybridized alkene bond and are usually consist of a SL of atoms structure into a honeycomb‐like structure will discuss in detail in next sections. [ 7–10 ]…”
Section: Introductionmentioning
confidence: 99%
“…Recently, many researchers are highly motivated on a wide range of 2D materials such as boron nitride (BN), graphite carbon nitride (g-C 3 N 4 ), and black phosphorus (BP) due to their favorable physicochemical properties that lead to their diverse applications in potential fields including photocatalysis, energy storage, biomedical applications, etc. (Khan et al 2019;Luo et al 2016;Naskar and Kim 2019a). The pioneer of this research, related to 2D materials, is of course graphene (Pattnaik et al 2016;Khan et al 2015;Huang et al 2012).…”
Section: Introductionmentioning
confidence: 99%